We have a system of equations 2x - 4y = 5 and 6x - 3y = 10.
We want to eliminate one variable when we add up the equations.
If we want to eliminate the x variable, we need to multiply the top, bottom or both of the equations with a number that when the equations are added together will eliminate the x variable.
Multiply the top equation by -3.
-3(2x - 4y) = 5 * -3
-6x + 12y = -15
Now when we add the two equations together, the x's will be eliminated.
-6x + 12y = -15
6x + 6y = 10
18y = -5
The x's were eliminated.